Prognostic significance of PD-L1 expression and CD8+ T cell infiltration in pulmonary neuroendocrine tumors - Haiyue Wang; Zhongwu Li; Bin Dong; Wei Sun; Xin Yang; Ruping Liu; Lixin Zhou; Xiaozheng Huang; Ling Jia; Dongmei Lin (BMC, 2018)
Abstract Background Recent research supports a significant role of immune checkpoint inhibitors in the treatment of solid tumors. However, relevant reports for programmed death-ligand 1 (PD-L1) and CD8+ tumor-infiltrating lymphocytes (TILs) in pulmonary neuroendocrine tumors (PNETs) have not been fully studied. Therefore, we investigated PNETs for the expression of PD-L1 and infiltration by CD8+ TILs as well as the prognostic value of both factors. Methods In total, 159 specimens of PNETs (35 TC, 2 AC, 28 LCNEC, 94 SCLC) were included in this study. Immunohistochemistry (IHC) was used to detect the expression of PD-L1 in these cases. Cases demonstrating ≥5% tumor cell expression or any expression (> 1%) of PD-L1 on immune cells were considered positive. CD8+ TILs both within stroma and tumor areas of invasive carcinoma were analyzed using whole-slide digital imaging. Manual regional annotation and machine cell counts were performed for each case. Results Positive expression of PD-L1 was observed in 72 cases (45.3%), including 9 cases (5.7%) with expression exclusively on tumor cells, 46 cases (28.9%) with expression exclusively on immune cells, and 17 cases (10.7%) with the expression on tumor cells and immune cells. PD-L1 expression was associated with necrosis (p < 0.001), high pathologic grade (p < 0.001) and histologic type (p < 0.001). No correlation was observed with overall survival (OS) (p = 0.158) or progression-free survival (PFS) (p = 0.315). In contrast, higher CD8+ T cell density was associated with the absence of vascular invasion (p = 0.004), histologic type (p = 0.005), negative lymph node metastasis (p = 0.005) and lower clinical staging (p = 0.007). Moreover, multivariate analysis revealed that CD8+ stromal TIL was an independent prognostic factor for improved OS (p = 0.009) and PFS (p = 0.002). Conclusion PD-L1 was expressed in approximately half of the PNETs. The majority of the expression was observed in immune cells. Positive expression of PD-L1 showed no correlation with OS or PFS, while higher CD8+ TILs within stroma was proved to be an independent prognostic factor for favorable OS and PFS of PNETs.